Effectiveness of interventions for the management of primary frozen shoulder: a systematic review of randomized trials. (1st September 2021) - Rex, Saleema S.; Kottam, Lucksy; McDaid, Catriona; Brealey, Stephen; Dias, Joseph; Hewitt, Catherine E.; Keding, Ada; Lamb, Sarah E.; Wright, Kath; Rangan, Amar
Abstract : Aims: This systematic review places a recently completed multicentre randomized controlled trial (RCT), UK FROST, in the context of existing randomized evidence for the management of primary frozen shoulder. UK FROST compared the effectiveness of pre-specified physiotherapy techniques with a steroid injection (PTSI), manipulation under anaesthesia (MUA) with a steroid injection, and arthroscopic capsular release (ACR). This review updates a 2012 review focusing on the effectiveness of MUA, ACR, hydrodilatation, and PTSI. Methods: MEDLINE, Embase, PEDro, Science Citation Index, Clinicaltrials.gov, CENTRAL, and the World Health Organization (WHO) International Clinical Trials Registry were searched up to December 2018. Reference lists of included studies were screened. No language restrictions applied. Eligible studies were RCTs comparing the effectiveness of MUA, ACR, PTSI, and hydrodilatation against each other, or supportive care or no treatment, for the management of primary frozen shoulder. Results: Nine RCTs were included. The primary outcome of patient-reported shoulder function at long-term follow-up (> 6 months and ≤ 12 months) was reported for five treatment comparisons across four studies. Standardized mean differences (SMD) were: ACR versus MUA: 0.21 (95% confidence interval (CI) 0.00 to 0.42), ACR versus supportive care: -0.13 (95% CI -1.10 to 0.83), and ACR versus PTSI: 0.33 (95% CI 0.07 to 0.59) and 0.25 (95% CI -0.34 to 0.85), all favouring ACR; MUA versus supportive care: 0 (95% CI -0.44 to 0.44) not favouring either; and MUA versus PTSI: 0.12 (95% CI -0.14 to 0.37) favouring MUA. None of these differences met the threshold of clinical significance agreed for the UK FROST and most confidence intervals included zero. Conclusion: The findings from a recent multicentre RCT provided the strongest evidence that, when compared with each other, neither PTSI, MUA, nor ACR are clinically superior. Evidence from smaller RCTs did not change this conclusion. The effectiveness of hydrodilatation based on four RCTs was inconclusive and there remains an evidence gap. Cite this article: Bone Jt Open 2021;2(9):773–784.